Reconceptualizing Political Obedience in Islamic Thought - Bachar Bakour (American Journal of Islam and Society)
This study examines the concept of obedience to the ruler in Islam focusing on prominent ḥadīth collections, primarily Ibn al-Athīr’s Jāmiʿ al-Uṣūl fī Aḥādīth al-Rasūl. It conducts a comprehensive textual and contextual analysis, extending its exploration to classical and contemporary works of Islamic political thought. The primary objective is to unveil insightful clues that contribute to a profound understanding of the concept of obedience, synthesizing original Islamic sources, historical experiences of the ummah, and the current realities of the Islamic world. The study argues that the concept of obedience emerges as conditional and contextual, balancing the rights of the ruler and the people. Also, the term ulū al-amr, symbolizing the joint effort of legislation, law enforcement, and adjudication, rejects autocratic power and political tyranny. Rulers are expected to consult with scholars, emphasizing a reciprocal relationship for the benefit of the ummah. The study further identifies a three-tiered classification of obedience: normative obedience rooted in love and respect for just rulers, obedience of necessity applied to corrupt rulers in Muslim history prior to the collapse of the Caliphate, and a form of emergency obedience to leaders in the contemporary era. On the basis of “averting harm takes priority over bringing the benefit” dictum, Islamic law has ordered that the despotism of the ruler, viewed as a fait accompli, is something that ought to be endured, and obedience given till the time is ripe for change.